PENGARUH â€œ SERING CETING â€ TERHADAP PENGETAHUAN IBU BALITA TENTANG STUNTING - Ni Nyoman Murti; Lamri Lamri; Cristinawati B/R Haloho (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2022)
In East Kalimantan, prevalence of stunting was increasing from 26.7% in 2015 becomes 30.8% in 2018. In 2019 from 10 regencies in East Kalimantan, prevalence in Kutai Kartanegara Regency 19.49% and prevalence in Balikpapan City placed in second to reach 18.48%. Stunting affects cognitive and physic of children, productvity declines, bad health and high risk to degenerative diseases. Survey of this research said that 3 from 5 mothers who has stunting baby, has no knowladge of stunting and what stunting is, meanwhile knowladge significantly effect on prevention and treatment stunting. There is an inovation of transfer knowladge about stunting called â€œSerInG CeTingâ€ which is unapplied in Health center of Baru Tengah so that the researcher want to analysis the effect of â€œSerInG CeTingâ€. This research used quasi eksperimen dengan one group pre-post test without control group design. Purpose of this research to influance analysis of â€œSerInG CeTingâ€ on Mothers. The sampling technique used total sampling with 38 mothers who have stunting toddler in Health Center of Baru Tengah in Mei 2022. The result of this research â€œSerInG CeTingâ€ is one of inovation which significanly increasing knowladge of mother in stunting with p value 0.000 < 0.05.